Ecological solid waste management literacy a measure of knowledge, attitudes, and practices - Biongcog, Jona Tejero (College of Home Economics, University of the Philippines Diliman, 2014)
This is a study using both quantitative and qualitative research methods conducted to: (1) determine the extent of ecological solid waste management knowledge, attitudes, and practices of secondary school students, faculty, and staff in Cabadbaran City, Agusan del Norte; and (2) to develop an Aptitude Test Scorecard that could be used by schools in assessing the students, faculty, and staff's extent of involvement in solid waste management (knowledge, attitudes, and practices). Five hundred nineteen (519) high school students, faculty and staff from Cabadbaran Agusan del Norte were chosen as respondents through complete enumeration (faculty and staff)and random sampling (students) using a researcher-designed survey questionnaire. Thirty percent of the high school students, all Technology and Livelihood Education teachers, and one staff per school were interviewed to elicit data on ecological solid waste management problems and possible programs that could be conducted within the school environment. A focus group discussion was utilized to validate the data gathered from the respondents of the study. Through the use of cluster analysis, the study was to identify four underlying clusters among the respondents. Using the characteristics generated and the researcher-analyst constructed typology, these four clusters of respondents were labeled as "disengaged", "uncommitted", "sensible", and "devoted". Findings revealed that out of 519 respondents, 30 % belong to cluster 1(the disengaged); 20 % in cluster 2 (the uncommitted); 35 % in cluster 3 (the sensible); and 15 % in cluster 4 (the devoted). Results show that respondents in cluster 1 have below average scores in knowledge, attitudes, and practices; cluster 2 have above average score in knowledge, but below average in attitudes and practices; cluster 3 have above average scores in knowledge, attitudes, and practices; and cluster 4 have below average score in knowledge but above average in attitudes and practices. An aptitude test on ecological solid waste management using the questions and logistic regression analysis was done on the data. The tool could be used to assess the students, faculty, and staff's level of involvement in ecological solid wasre management activities.